Factors that Influence Profitability of General Insurance Issuers in Indonesia - Elisabeth, Ermy; Mulyana, Bambang (The Economics and Finance Letters, 2019)
This research aims to examine and to analyze factors that influence profitability of general insurance issuers in Indonesia. Factors that are examined consist of activity (working capital turnover), liquidity (current ratio), solvency (risk based capital) and profitability (net profit margin, return on investment and return on equity). Research data is quarterly data for five year period (March 2012 to December 2016). The purposive sampling method was used from a population comprising 14 general insurance issuers with outcome of 5 issuers that met the criteria. Using the multiple linear regression method of analysis for panel data, the results revealed that the variables of the working capital turnover, current ratio and risk based capital simultaneously influenced profitability (net profit margin, return on investment, return on equity) while working capital turn over influenced profitability (net profit margin, return on investment and return on equity) only partially. Current ratio also influenced profitability ratio (net profit margin and return on equity) however, Risk Based Capital did not influence all profitability ratios. The results of the study indicate that Insurance companies should increase their sales in order to get a higher working capital, maintain a liquidity ratio and achieve solvency ratio according to the regulations.